Complex Probability and Markov Stochastic Process - Bidabad, Bijan; Bidabad, Behrouz (Indian Journal of Finance and Banking, 2019)
This note discusses the existence of "complex probability" in the real world sensible problems. By defining a measure more general than the conventional definition of probability, the transition probability matrix of discrete Markov chain is broken to the periods shorter than a complete step of the transition. In this regard, the complex probability is implied.